2008
DOI: 10.1111/j.1365-2125.2008.03140.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic/ pharmacodynamic analysis of CCR5 receptor occupancy by maraviroc in healthy subjects and HIV‐positive patients

Abstract: BACKGROUNDMaraviroc, a noncompetitive antagonist of the CCR5 coreceptor, was recently approved in the USA as a treatment of HIV infection. For antiretroviral agents that target the virus, antiviral effect can be related to some extent to plasma drug concentrations. For CCR5 antagonists that target the host cells, receptor occupancy in vivo might be a better predictor of efficacy. AIMSTo develop a population pharmacokinetic (PK)-pharmacodynamic (PD) model that describes CCR5 receptor occupancy by maraviroc afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…This observation is consistent with clinical studies showing that almost complete CCR5 occupancy is required to significantly reduce plasma viremia (29) and suggests that only a few unoccupied receptors may be sufficient to initiate and sustain a spreading infection. However, as with human CCR5, rhesus CCR5 was not fully internalized by MIP-1␤ in PBMCs or rectal leukocytes in the in vitro assay, thus limiting our analysis to the proportion of CCR5 that was downregulated by MIP-1␤ ex vivo (31).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This observation is consistent with clinical studies showing that almost complete CCR5 occupancy is required to significantly reduce plasma viremia (29) and suggests that only a few unoccupied receptors may be sufficient to initiate and sustain a spreading infection. However, as with human CCR5, rhesus CCR5 was not fully internalized by MIP-1␤ in PBMCs or rectal leukocytes in the in vitro assay, thus limiting our analysis to the proportion of CCR5 that was downregulated by MIP-1␤ ex vivo (31).…”
Section: Discussionsupporting
confidence: 78%
“…The binding of MVC to CCR5 was determined ex vivo using a MIP-1␤ internalization assay previously described (27)(28)(29). In this assay, free CCR5 receptors in the cell surface are internalized upon stimulation with MIP-1␤, which is a natural ligand of CCR5 (30).…”
Section: Methodsmentioning
confidence: 99%
“…Maraviroc dose selection for the phase 2b/3 trials was based on in vitro virology (in vitro protein-adjusted IC 90 = 2.1 ng/ml) (Dorr et al, 2005), PK-viral dynamics modeling utilizing a broad range of doses in monotherapy (in vivo IC 50 of 8 ng/ml) (Rosario et al, 2008), and an extensive healthy volunteer drug interaction program (Abel et al, 2009). In a maraviroc monotherapy study, greater than 80% viral inhibition (range: 88-96%) was demonstrated with PK-viral dynamics modeling at exposures observed with 300 mg BID (C avg [AUC divided by the dosing interval] range: 141-338 ng/ml) (Fatkenheuer et al, 2005;Rosario et al, 2006).…”
mentioning
confidence: 99%
“…RO assays are typically performed on fresh blood specimens in order to minimize the probability of drug dissociation from target receptors during sample processing. Current efforts to stabilize blood with traditional paraformaldehyde‐based fixatives often lead to unacceptable levels of signal loss or increased background staining levels 59. Ultimately, the ability to more effectively stabilize blood specimens immediately following collection would likely reduce variability and enable for a more quantitative assessment of RO.…”
Section: Future Perspectivesmentioning
confidence: 99%